Spread of Macrophomina phaseolina in varied sorghum genotypes under depleting soil moisture during post monsoon rain fed conditions - and M. Y. SAMDUR, ASHOK V. GADEWAR* (Indian Phytopathology, 2012)
Biological process of aging in sorghum results into leaf senescence that in turn creates favourable conditions for Macrophomina phaseolina. The cortical lesion caused by Macrophomina phaseolina on sorghum plant developed rapidly as the aging advanced yet not as a rule. In 41.3% of genotypes plant age did not affect Macrophomina advancement i.e. increase in age of the plant neither deterred or favoured the growth of Macrophomina indicating constant conducive growth environment all through life of plants. Observations revealed that about 50 per cent of leaves senesce as plant reaches to flowering and maintaining green leaves that is associated with rate of senescence has close relationship with charcoal rot incidence in field. Slow rate of leaf senescence tend to contribute to lower charcoal rot incidence and also sorghum genotypes that show minimum more than 5 per cent green leaves at terminal age have a tendency to give lesser incidence of charcoal rot . Present investigation also reveals perfect relation among senescence, charcoal rot and lesion length. This association could be recorded in 34.5 per cent genotypes. Some genotypes having lower cortical lesion length showed lower charcoal rot and lower senescence whereas other genotypes showing the higher lesion length also showed higher charcoal rot and higher senescence.